2019
DOI: 10.1093/scan/nsz040
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of theory-of-mind are associated with variation in children’s everyday social cognition

Abstract: Theory of mind (ToM), the capacity to reason about others’ mental states, is central to healthy social development. Neural mechanisms supporting ToM may contribute to individual differences in children’s social cognitive behavior. Employing a false belief functional magnetic resonance imaging paradigm, we identified patterns of neural activity and connectivity elicited by ToM reasoning in school-age children (N = 32, ages 9–13). Next, we tested relations between these neural ToM correlates and children’s every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 56 publications
(87 reference statements)
2
14
0
Order By: Relevance
“…The current results showing increased amplitudes at both hemispheres can potentially be linked to the results of the eLORETA analyses which showed that third-order trials consistently elicited the strongest activation in the PCC, the cuneus, as well as the TPJ, all regions of the established ToM network (see e.g., Abu-Akel and Shamay-Tsoory, 2011). The cuneus and the TPJ were previously associated with processing others' mental states (e.g., Saxe and Kanwisher, 2003;Schlaffke et al, 2015;Lin et al, 2018;Boccadoro et al, 2019;Mukerji et al, 2019), whereas the TPJ was additionally associated with other cognitive functions such as attention, memory, and language processing (e.g., Igelström et al, 2015). The PCC together with the precuneus, on the other hand, was previously associated with processing mental states of oneself (Lou et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The current results showing increased amplitudes at both hemispheres can potentially be linked to the results of the eLORETA analyses which showed that third-order trials consistently elicited the strongest activation in the PCC, the cuneus, as well as the TPJ, all regions of the established ToM network (see e.g., Abu-Akel and Shamay-Tsoory, 2011). The cuneus and the TPJ were previously associated with processing others' mental states (e.g., Saxe and Kanwisher, 2003;Schlaffke et al, 2015;Lin et al, 2018;Boccadoro et al, 2019;Mukerji et al, 2019), whereas the TPJ was additionally associated with other cognitive functions such as attention, memory, and language processing (e.g., Igelström et al, 2015). The PCC together with the precuneus, on the other hand, was previously associated with processing mental states of oneself (Lou et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…SC involves a broad range of neural regions and networks in stimulus processing in the central nervous system. Neuroimaging studies represent an important tool for the comprehension of the neural bases that explain the mechanisms of SC, since they can provide not only an assessment of brain anatomy but also of neural activity in specific regions as well as its relations (65)(66)(67)(68)(69). In this sense, the use of structural Magnetic Resonance Imaging (sMRI) and functional Magnetic Resonance Imaging (fMRI) has become a fundamental strategy for understanding these neural bases, as well as for studying psychiatric diseases that classically present alterations in SC, such as ASD and SSD (70)(71)(72)(73).…”
Section: Neuroanatomical and Neurofunctional Brain Markers Of Social mentioning
confidence: 99%
“…Similarly, Richardson and colleagues (2018) detected increasing connectivity with age between temporoparietal junction, precuneus and medial prefrontal cortex in children aged 3 to 12 years of age during an implicit Theory of Mind task (i.e., watching a movie that elicits mentalizing). Again other studies reported no age effects in connectivity during mentalizing, but stable connectivity patterns between areas associated with mentalizing (e.g., medial prefrontal cortex, temporoparietal junction, precuneus) and striatum/dorsolateral prefrontal cortex (McCormick et al, 2018;in 8 to 16-year-olds) or within mentalizing regions (temporoparietal junction, superior temporal sulcus, precuneus (Mukerji et al, 2019); in 9 to 13-year-olds). Such differences in findings may arise due to variations in the tasks employed or the characteristics of the sample studied, e.g., the age range.…”
Section: Early Neuronal Continuity Of Mentalizing 28mentioning
confidence: 88%